Practical justice living off-center in a self-centered world - Blue, Kevin (Downers Grove, Ill. : InterVarsity Press, 2006)
We are well-intended, but stuck in the rut of the everyday. We want to make our lives matter. But we don't know where to start. We wonder about everything from whether to give a dollar to a beggar to how to participate in the political process; from whether to shop at Wal-Mart to how much to spend on a car. Kevin Blue has spent his adult life answering these questions for himself and for others. He lives in the heart of Los Angeles, where these questions can't be set aside. And he has led college students through experiences in urban ministry as well as international treks to the poorest parts of the world. In Practical Justice he combines what he has learned with the experiences of others to answer your questions.
Introduction: getting your house in order -- God's forgotten ones -- Should I help? -- Count the cost -- Giving a man a fish : direct relief -- Teaching a man to fish : distributing skills -- Fixing the pond : dealing with the system -- Race and class -- A life of justice -- The coming of trouble -- Not becoming what you hate -- Finishing the race -- A closing word.
"Likewise"--Prelim. p.
Includes bibliographical references (p. 139-143).
Description based on print version record.
Keywords: Christian life; City missions; Christianity and justice; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books